1998
DOI: 10.1039/a805225e
|View full text |Cite
|
Sign up to set email alerts
|

Pour on application of growth promoters in veal calves: analytical and histological results†

Abstract: To investigate the possibilities for screening and confirmation methods when the 'pour on' method of application is used for administration of growth promoters, an animal experiment was performed using a cocktail of a combination of growth promoters derived from (illegal) practice. Two cocktails were used, cocktail A consisting of stanozolol and estradiol benzoate and cocktail B consisting of stanozolol, estradiol benzoate and beclomethasone dipropionate. The intended dose per animal was 110 mg stanozolol, 25 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 3 publications
3
15
0
Order By: Relevance
“…Although it has long been recognised that synthetic glucocorticoids have immunosuppressive activities, dexamethasone and other corticosteroids are frequently used as illegal growth promoters in livestock production, because of improved feed intake, increased live weight gain, reduced feed conversion ratio, reduced nitrogen retention and increased water retention and fat content (Istasse et al., 1989). A few studies have shown a significant reduction of the thymic tissue, namely cortical atrophy and fatty infiltration, following the use of therapeutic doses of synthetic corticosteroid (Guarda et al., 1983, 1990; Groot et al., 1998; Schilt et al., 1998). These findings have been correlated with apoptosis of thymocytes (Sun et al., 1992), a finding also related to elevated endogenous corticosterone levels in mice (Gruber et al., 1994; Tarcic et al., 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Although it has long been recognised that synthetic glucocorticoids have immunosuppressive activities, dexamethasone and other corticosteroids are frequently used as illegal growth promoters in livestock production, because of improved feed intake, increased live weight gain, reduced feed conversion ratio, reduced nitrogen retention and increased water retention and fat content (Istasse et al., 1989). A few studies have shown a significant reduction of the thymic tissue, namely cortical atrophy and fatty infiltration, following the use of therapeutic doses of synthetic corticosteroid (Guarda et al., 1983, 1990; Groot et al., 1998; Schilt et al., 1998). These findings have been correlated with apoptosis of thymocytes (Sun et al., 1992), a finding also related to elevated endogenous corticosterone levels in mice (Gruber et al., 1994; Tarcic et al., 1998).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, N/N+C ratio was lower in treated groups than in the control group. The evident tendency of the value may suggest that, following the administration of androgens, [15,20]. As testosterone is the primary substrate for the synthesis of estradiol in the male, the aromatization of BOL and ADD could produce sufficient estradiol to induce the urothelial cell swelling.…”
Section: Discussionmentioning
confidence: 99%
“…Oestrogenic hormones induce characteristic lesions consisting of squamous metaplasia in the glandular tissue of the prostate and bulbourethral glands of male animals and in Bartholin's glands in females (Kroes, 1970;Gropp et al, 1976;Schaudinn and Beck, 1977;Grandmontagne, 1986;Deschamps et al, 1987;Rosmini, 1987;Groot et al, 1989;Girardi et al, 1990;Groot en den Hartog, 1990;Biolatti et al, 1994;Finazzi et al, 1993;Schilt et al, 1998;Groot et al, 2000).…”
Section: Introductionmentioning
confidence: 99%